A human surrogate neck for traumatic brain injury research - Farmer, Jon; Mitchell, Sean; Sherratt, Paul; Miyazaki, Yusuke (Frontiers in Bioengineering and Biotechnology, 2022)
Properties of the human neck such as range and resistance to motion are considered important determinants of the kinematic response of the head pre, during and post-impact. Mechanical surrogate necks (i.e., anthropomorphic test device necks), have generally been limited to a single anatomical plane of motion and an artificially high resistance to motion. The aim of this study was to present the Loughborough University Surrogate Neck that is representative of the 50th percentile human male neck, developed for motion in and between each of the anatomical planes with inertial and flexural stiffness properties matching those of a passive elastic (i.e., negligible active tension) neck muscle state. The complex intervertebral joints were reduced to three encapsulated ball joints with appropriate locations, orientations and distributed range of motion to precisely position and orientate the head with respect to the torso at the neutral position and end range of motion. A plain bearing sub-assembly was incorporated at the C1-C2 vertebral level to permit 50% of the axial rotation with negligible resistance to motion, as exhibited by humans. Detachable elastomeric elements provided resistance to motion across each ball joint and permit any orientation of the head within the physiological range of motion of the joints. The mass of the surrogate neck (1.62 Kg) was in agreement with the typical human range and similar agreement was found for the principal moments of inertia (Ixx 26.8 kg cm2, Iyy 20.5 kg cm2 and Izz 14.3 kg cm2). Quasi-static bending moment and dynamic torque tests characterised the surrogate neck in flexion/extension, lateral flexion and axial rotation. With respect to commercial surrogate necks, the surrogate neck presented here was in closer agreement to the reported human responses, for equivalent loading conditions. The applications of a surrogate neck that can appropriately constrain the head relative to the torso are far reaching in the areas of brain injury mechanism research, and for the development and assessment of protective equipment to reduce the risk of such injuries.